The Impact of Social Media Activism on Equity-Focused Educational Reform Movements - Arna Almaidah Saputri; Lailatul Fitriyah; Candra Yuniantika; Esa Lisani Rohima (Education : Jurnal Sosial Humaniora dan Pendidikan, 2026)
Social media has become largely a place for educational activism and debate, particularly in promoting equity-driven reforms. Twitter and TikTok are used intensively by online communities to highlight educational inequities and influence public perception. This study aims to uncover how social media activism, through specific framing tactics, leads to policy debate and institutional response in the face of equitable education reform. A single qualitative case study was conducted through the analysis of 120 TikTok clips, 87 Twitter threads, and 12 semi-structured interviews with digital education activists. NVivo was utilized for thematic analysis to ascertain framing strategies that are most prevalent and issue clusters. The findings suggest that TikTok primarily uses motivational framing to establish emotional engagement, while Twitter uses diagnostic and prognostic framing to define structural problems and propose policy remedies. Three-level framing (diagnostic, prognostic, motivational) was found to be the most effective way of mobilizing public engagement and provoking institutional response.Five issues rooted in necessities available on platforms are inequity of access, curricular bias, minority underrepresentation, symbolic violence in schools, and the invisibility of the budget. The study adds to the theory of framing by placing the deployment of its conceptualisation in digital education activism and has practical implications for educators, policymakers, and civil society actors to build educational equity through participatory digital platforms.